The Influence of Organizational Support, Attitudes toward Technology Use, Perceived Usefulness, and Perceived Ease of Use on Employees’ Innovative Work Behavior at ABC Company - Chaiturdkiet, Wisit; Rungrueng, Patarada; Myint Naing, Phyu Phyu (Journal of Business Administration The Association of Private Higher Education Institutions of Thailand, 2026)
perceived usefulness, and innovative behavior in the workplace; and (2) investigate the influence of organizational support, attitude toward technology use, perceived usefulness, and perceived ease of use on employees’ innovative behavior at ABC Company, a Thai medical device manufacturer with over 50 years of experience that is currently adapting to digital technology in its operations. The sample consisted of 88 employees from ABC Company. A questionnaire was used as the data collection instrument. The data were analyzed using descriptive statistics, including frequency, percentage, mean, and standard deviation, as well as inferential statistics, including Pearson’s correlation coefficient and multiple regression analysis. The results indicated that: (1) Pearson’s correlation analysis revealed that all variables organizational support, attitude toward technology use, perceived ease of use, and perceived usefulness were positively and significantly related to innovative behavior in the workplace at the 0.01 level. Among these, perceived ease of use showed the strongest relationship (r = 0.837); and (2) the multiple regression analysis demonstrated that the model explained 57.6% of the variance in innovative work behavior (R² = 0.576), which was statistically significant at the 0.05 level. The predictors, ranked in descending order of significance, were perceived usefulness (β = 0.63), attitude toward technology use (β = 0.337), and perceived ease of use (β = 0.196). These findings suggest that organizations should prioritize the development of user-friendly technologies that deliver tangible benefits, alongside supportive organizational policies, in order to foster innovative behavior among employees and enhance long-term organizational competitiveness.